ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMP PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Rima Rismawati; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to determine the mathematical problem solving abilities of junior high school students in West Bandung Regency with indicator of student’s mathematical problem solving abilities used are to identify known data, data asked, sufficient data for problem solving, identifying strategies that can be taken, completing mathematical models accompanied by reasons, check the correctness of the solution obtained. This research was conducted on 20 students in one of the junior high school in The Cililin District West Bandung Regency using a qualitative descriptive method. The instrument used in the form of 5 items about mathematical problem solving skills in the material System of Two Variable Linear Equations. The conclusion of this study is that the mathematical problem solving ability of junior high school students in Cililin District is still low.